Disability, home physical environment and non-fatal injuries among young children in China. - Hui-ping Zhu (Public Library of Science (PLoS), 2012)
Objectives We compared the patterns of medically attended injuries between children with and without disabilities and explored the residential environment risks in five counties of Hubei Province in the People's Republic of China by a 1:1 matched case-control study based on the biopsychosocial model of the International Classification of Functioning, Disability and Health--ICF. Methods 1201 children aged 1-14 with disabilities and 1201 their healthy counterparts matched as having the same gender, same age, and lived in the same neighborhood were recruited in our study. Characteristics of injuries in the past 12 months were compared between children with and without disabilities. The associations among disability status, home environment factors and injuries were examined in logistic regression analysis taking into account sociodemographic factors. Results Children with disabilities had a significantly higher prevalence of injury than children without disabilities (10.2% vs. 4.4%; P<.001). The two groups differed significantly in terms of number of injury episodes, injury place and activity at time of injury. Falls were the leading mechanism of injury regardless of disability status. Most of the injury events happened inside the home and leisure activities were the most reported activity when injured for both groups. The univariate OR for injury was 4.46 (2.57-7.74) for the disabled children compared with the non-disabled children. Disabled children whose family raised cat/dog(s) were 76% more likely to be injured during the last 12 months (OR = 1.76; 95% CI = 1.02, 3.02), comparing with those whose family did not have any cat/dog. And for children without disabilities, those whose family had cat/dog(s) were over 3 times more likely to having injuries comparing with those whose family did not have any cat/dog. Conclusions Children with disabilities had a significantly increased risk for injury. Interventions to prevent residential injury are an important public health priority in children with disabilities.